Predictors of burnout among US healthcare providers: a systematic review. Issue 8 (25th August 2022) - Meredith, Lisa S; Bouskill, Kathryn; Chang, Joan; Larkin, Jody; Motala, Aneesa; Hempel, Susanne
Abstract : Objective: One potential barrier to optimal healthcare may be provider burnout or occupational-related stress in the workplace. The objective of this study is to conduct a systematic review to identify the predictors of burnout among US. healthcare providers. Design: Systematic review using in-depth critical appraisal to assess risk of bias and present the quality of evidence in synthesised results from the prognostic studies. Data sources: We searched 11 databases, registries, existing reviews and contacted experts through 4 October 2021. Eligibility criteria for selecting studies: We included all studies evaluating potential predictors and documenting the presence and absence of associations with burnout assessed as a multidimensional construct. We excluded studies that relied solely on a single continuous subscale of burnout. Data were abstracted from eligible studies and checked for accuracy by a content expert and a methodologist. Data extraction and synthesis: Two reviewers independently screened citations and full-text publications using predetermined eligibility criteria. Results: The 141 identified studies evaluated a range of burnout predictors. Findings for demographic characteristics were conflicting or show no association. Workplace factors, such as workload, work/life balance, job autonomy and perceived support from leadership, had stronger associations with risk for burnout. Mental health factors, such as anxiety, and physical health risks may increase the risk, although the direction of these associations is unclear as few prospective studies exist to address this question. Factors such as social support appear to have a protective effect. Conclusion: We found the most evidence for workplace, mental health and psychosocial factors in predicting burnout but limited evidence for other potential predictors. However, more prospective studies are needed to improve our understanding about how to prevent provider burnout. PROSPERO registration number: CRD4202014836.